Scooby-Doo! and the samurai ghost - McCann, Jesse Leon; Cartoon Network (Television network) (New York : Scholastic, 2005)
Scooby-Doo and his friends from Mystery, Inc. go to Japan to investigate the mystery of a ghost of an ancient samurai who haunts a construction site.
"Cartoon Network."
"WB Worldwide Publishing."
1.
004-008.
86084
Keywords: Scooby-Doo (Fictitious character) -- Juvenile fiction; Ghosts -- Japan -- Juvenile fiction; Samurai -- Juvenile fiction; Dogs -- Juvenile fiction; Scooby-Doo (Fictitious character) -- Fiction; Ghosts -- Fiction; Samurai -- Fiction; Dogs -- Fiction; Mystery and detective stories; Japan -- Juvenile fiction; Japan -- Fiction; Ghost stories; Mystery fiction; Radio and television novels